Training to be a spinal endoscopic surgeon: What matters? - Xie, Yizhou; Zhou, Qun; Wang, Yongtao; Feng, Chengzhi; Fan, Xiaohong; Yu, Yang (Frontiers in Surgery, 2023)
Objective Spinal endoscopic surgery has been promoted rapidly in the past decade, attracting an increasing number of young, dedicated surgeons. However, it has long been denounced for its long learning curve as a factor impeding the development of this state-of-the-art technique. The aim of the present study was to discover what really matters in the educational process of becoming a spinal endoscopic surgeon. Methods An online survey consisting of 14 compulsory questions was distributed in April and May 2022 through the First Chinese Spinal Endoscopic Surgeons Skills Competition. Reminders were sent to increase response rates. Results Of the 893 emails that were sent, we received 637 responses. A total of 375 (76.7%) surgeons most frequently used endoscopic techniques in their practices. Regardless of their different backgrounds, 284 (75.7%) surgeons thought it would be necessary for a young spinal endoscopic surgeon to perform 300 cases independently in order to become proficient, followed by 500 (n=43, 11.5%), 100 (n=40, 10.7%), and 1,000 (n=8, 2.1%) cases. According to the surgeons, the most difficult aspect of mastering the endoscopic technique is a disparate surgical view (n=255, 68%), followed by adaption to new instruments (n=86, 22.9%) and hand-eye coordination (n=34, 9.1%). The most helpful training method for helping the spinal endoscopic surgeons of younger generations improve is operating on simulation models or cadaver courses (n=216, 57.6%), followed by online or offline theoretical courses (n=67, 17.9%), acquiring opportunities during surgeries (n=51, 13.6%), and frequently participating in surgeries as an assistant (n=41, 10.9%). Conclusion From the perspective of surgeons, to be skilled in spinal endoscopic surgery means overcoming a steep learning curve. However, training systems should be given more attention to make them more accessible to younger surgeons so they can work on simulation models or take cadaver courses.